Phragmen-Lindelof Principle for Some Quasilinear Evolution Equations of the Second Order - Sleptsova, I. P.; Shishkov, A. E. (Ukrains’kyi Matematychnyi Zhurnal, 2005)
We consider the equation $u_{tt} + A (u_t) + B(u) = 0$, where $A$ and $B$ are quasilinear operators with respect to the variable x of the second order and the fourth order, respectively. In a cylindrical domain unbounded with respect to the space variables, we obtain estimates that characterize the minimum growth of any nonzero solution of the mixed problem at infinity.